2011
DOI: 10.1590/s0100-29452011000500088
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento de maracujazeiro-amarelo enxertado sobre maracujazeiro-doce em diferentes espaçamentos de plantio

Abstract: RESUMO - GROWTH OF YELLOW PASSION FRUIT GRAFTED ON SWEET PASSION FRUIT IN DIFFERENT PLANTING SPACING ABSTRACT -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
0
6
0
1
Order By: Relevance
“…In Adamantina, SP, with traditional grafted seedlings, Nasser et al (2011) evaluating the planting line spacing 1.0; 1.5; 2.0; 3.0; 4.0 and 5.0 m; and 3.2 m between lines, also found lower SBL when they used 1.5 x 3.2 m between plants, with 139.1 cm, differing from the 3.0 and 4.0 m spacing, with 191.0 and 189.8 cm, respectively. These authors also observed higher PSD with the use of less dense spacing, 4.0 x 3.2 m, 30.4 mm compared to 1.0 x 3.2 m and 2.0 x 3.2 m, respectively, 22.75 and 24.5 mm at 360 days after transplantation (DAT).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Adamantina, SP, with traditional grafted seedlings, Nasser et al (2011) evaluating the planting line spacing 1.0; 1.5; 2.0; 3.0; 4.0 and 5.0 m; and 3.2 m between lines, also found lower SBL when they used 1.5 x 3.2 m between plants, with 139.1 cm, differing from the 3.0 and 4.0 m spacing, with 191.0 and 189.8 cm, respectively. These authors also observed higher PSD with the use of less dense spacing, 4.0 x 3.2 m, 30.4 mm compared to 1.0 x 3.2 m and 2.0 x 3.2 m, respectively, 22.75 and 24.5 mm at 360 days after transplantation (DAT).…”
Section: Resultsmentioning
confidence: 99%
“…These authors also observed higher PSD with the use of less dense spacing, 4.0 x 3.2 m, 30.4 mm compared to 1.0 x 3.2 m and 2.0 x 3.2 m, respectively, 22.75 and 24.5 mm at 360 days after transplantation (DAT). Using traditional seedlings and evaluating the development of grafted passion fruit, Cavichioli et al (2011) reported superior SBL value, 337.4 cm at 150 days after sowing (DAS) and the primary stem diameter of 30.6 mm at 360 DAS on an ungrafted plant. Possibly, in addition to the difference of seedling type and transplantation period that allows great plant development period in the field.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiment was conducted in the municipality of Remanso -BA (coordinates: 09°37'47.1"S; 42°04'56.7"W, altitude: 399 m), the Lower Basin of the São Francisco Valley, left bank of the Sobradinho Lake, in a soil classified as Regolithic Neossol (SANTOS et al, 2012) The seedlings were grown in the nursery of the Department of Technology and Social Sciences of the University of the State of Bahia -DTSS/USB, and 80 days after emergence they were transplanted into planting holes prepared in spacing of 2.5 m x 4.0 m, 50 x 50 x 50 cm for the conventional system of planting and 50 x 50 x 60 cm for the cultivation system in polyethylene bags.…”
Section: Methodsmentioning
confidence: 99%
“…One of the initial measures is the use of materials adapted to the growing region, seeing that the quality of production is linked to genetic factors (genotypes and plant age), as well as to environmental factors (location and growing season, light and radiation exposure, and temperature) and agronomic (salinity, water management, plant nutrition, biostimulants and microbial inoculants, soil management, and harvest) (Vitorri et al, 2018). In order to improve the nutrient content of the fruits, it is necessary to increase the productivity of the plants (Andrade Junior et al, 2003;Nasser et al, 2011). In this context, Figueiredo et al (2015) and Weber et al (2016) conducted an experiment in vertical espalier with populations of one and two plants per pit and did not observe significant variations in the physical and physical-chemical properties in the passion fruit, but concluded that there may be gain in productivity.…”
Section: Introductionmentioning
confidence: 99%